Creativity and involvement in art in different types of synaesthesia. (28th November 2018) - Lunke, Katrin; Meier, Beat
Abstract : The aim of the present study was to test the relationship between different types of synaesthesia and their involvement in art, creative, and visual abilities. We tested 20 grapheme‐colour, 18 sound‐colour, 19 grapheme‐colour‐and‐sound‐colour, 20 sequence‐space synaesthetes, and the same number of controls matched by age, gender, and education. We assessed the number of artistic professions, involvement in art, and the performance in psychometric tests of divergent and convergent creativity, as well as visual and visuo‐spatial abilities. Results show a higher prevalence of artists among synaesthetes, especially sound‐colour synaesthetes. Sound‐colour synaesthetes also showed a higher involvement in artistic activities overall while sequence‐space synaesthetes showed higher involvement in visual art. Only grapheme‐colour‐and‐sound‐colour synaesthetes showed significantly higher divergent creativity compared to matched controls. Additionally, overall, synaesthetes scored higher in visuo‐spatial abilities (i.e., mental rotation). For synaesthetes and controls, visuo‐spatial abilities correlated with divergent creativity. We discuss that synaesthetes' higher involvement in art is not necessarily reflected in their basic creative abilities.